2015
DOI: 10.15537/smj.2015.12.12264
|View full text |Cite
|
Sign up to set email alerts
|

The association between the CC chemokine ligand 5 -28C>G gene polymorphism and tuberculosis susceptibility

Abstract: Objectives:To assess the association between chemotactic chemokine (C-C motif) ligand 5 (CCL5) -28C>G polymorphism and tuberculosis (TB) risk.Methods:PubMed, Web of Science, and WanFang were searched up to April 2015 for eligible studies on CCL5 -28C>G polymorphism. Data was extracted, and pooled odd ratios (ORs) as well as 95% confidence intervals (95% CI) were calculated.Results:Eight case-control studies were extracted from 8 articles on the polymorphism involving 1852 TB cases and 2068 controls. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…For example, interferon gamma ( IFNG ) and interleukin 17 ( IL17 ) polymorphisms were reported to be associated with TB risk 7,8 . Several meta-analyses suggested that cytokines such as IL10, IL12B, IL27 and CC chemokine ligand 5 (CCL5) play important roles in the progression of TB 912 . Indeed, genetic variants in cytokine genes could affect the recognition sites of the transcription factors, leading to altered transcriptional activity, which may then result in a change in cytokine production levels 13 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, interferon gamma ( IFNG ) and interleukin 17 ( IL17 ) polymorphisms were reported to be associated with TB risk 7,8 . Several meta-analyses suggested that cytokines such as IL10, IL12B, IL27 and CC chemokine ligand 5 (CCL5) play important roles in the progression of TB 912 . Indeed, genetic variants in cytokine genes could affect the recognition sites of the transcription factors, leading to altered transcriptional activity, which may then result in a change in cytokine production levels 13 .…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the article by Lu et al 1 published in this journal. In their systematic review and meta-analysis, the authors assessed the association between chemotactic chemokine (C-C motif) ligand 5 (CCL5) -28C>G polymorphism and tuberculosis (TB).…”
mentioning
confidence: 99%